Teacher evaluation system, institutions of technology higher education: quality guidelines - Parada Romero, Laura Belkis (Universidad Pedagógica y Tecnológica de Colombia, 2016)
Due to the globalization of education, it has become prevalent to strengthen the quality systems to ensure that educational actors in higher education institutions are the best. In this context teachers are given a main role since they are cornerstones in educational processes. Currently, teacher quality is assessed through an assessment or evaluation system. Almost every university evaluates its teachers, but there is no legal regulation on how to do it, in most institutions there is a professional in charge of designing and applying assessment instruments according to the authors he/she prefers. In most universities, on the one hand, it is used a traditional questionnaire aiming to collect data about dimensions associated with teaching, on the other hand, there is another option in which assessment models include self-evaluation, as in some cases in Chile. That’s why one of the concerns of this research is to propose guidelines for a more qualitative and formative assessment not exclusively following political parameters –based on administrative decisions–, but following emerging proposals with a deeper analysis. Nowadays the main actors in teacher evaluation are teachers, students and administrative staff, every six months these actors are evaluated by using an assessment tool that they usually do not know. The research investigates the perception actors in teacher evaluation have regarding its objectives, methods and stages, so they put forward ideas on how to restructure the current institutional assessment and propose improvements aiming at both the quantitative aspect and the qualitative analysis of performances and skills.